KESADARAN HUKUM PELAKU USAHA/UMKM TERHADAP KEWAJIBAN PRODUK BERSERTIFIKASI HALAL DI INDONESIA - Syafa Maura, Meidyna; Makhfiyyani, Kanzani; Syarif Hidayatullah, Maulana (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This study aims to analyze the level of legal awareness of business actors, especially MSMEs, towards the obligation of halal certification in Indonesia. The method used is a literature study from journals accessed through the Publish or Perish application with sources from Google Scholar and Semantic Scholar. Through a comprehensive literature review from various scientific journals, it was found that the legal awareness of business actors regarding halal certification is still relatively low. Some of the factors that affect include a lack of understanding of halal certification regulations, the assumption that the halal certification process is complicated and requires a large cost, and the lack of supervision and law enforcement from the government.